The gut microbiota-brain axis in behaviour and brain disorders - Morais, Livia H; Schreiber, 4th, Henry L; Mazmanian, Sarkis K (Nature reviews. Microbiology, 2021)
In a striking display of trans-kingdom symbiosis, gut bacteria cooperate with their animal hosts to regulate the development and function of the immune, metabolic and nervous systems through dynamic bidirectional communication along the 'gut-brain axis'. These processes may affect human health, as certain animal behaviours appear to correlate with the composition of gut bacteria, and disruptions in microbial communities have been implicated in several neurological disorders. Most insights about host-microbiota interactions come from animal models, which represent crucial tools for studying the various pathways linking the gut and the brain. However, there are complexities and manifest limitations inherent in translating complex human disease to reductionist animal models. In this Review, we discuss emerging and exciting evidence of intricate and crucial connections between the gut microbiota and the brain involving multiple biological systems, and possible contributions by the gut microbiota to neurological disorders. Continued advances from this frontier of biomedicine may lead to tangible impacts on human health.